A phase II study of pazopanib as front-line therapy in patients with non-resectable or metastatic soft-tissue sarcomas who are not candidates for chemotherapy. (September 2020) - Hirbe, Angela C.; Eulo, Vanessa; Moon, Chang I.; Luo, Jingqin; Myles, Stephanie; Seetharam, Mahesh; Toeniskoetter, Jacqui; Kershner, Tammy; Haarberg, Sasha; Agulnik, Mark; Monga, Varun; Milhem, Mohammad; et al.
Abstract: Background: Cytotoxic chemotherapy remains the standard of care first-line treatment for advanced and metastatic soft-tissue sarcomas (STSs). Certain patients may not be chemotherapy candidates based upon age or co-morbidities, leaving limited treatment options. Pazopanib is a multi-targeted tyrosine kinase inhibitor that is FDA-approved for metastatic STS after the first line. We proposed a phase II study evaluating pazopanib as a first-line agent in patients with advanced disease who are deemed not to be candidates for chemotherapy. Methods: Eligible patients were at least 18 years old, not candidates for chemotherapyand were treatment naive. Pazopanib was titrated from 200 mg twice daily to a goal of 800 mg daily. The primary end point was the clinical benefit rate (CBR) (CBR = completed response + partial response + stable disease per Response Evaluation Criteria in Solid Tumours [RECIST 1.1]) at 16 weeks. The sample size of 56 evaluable patients was calculated to provide 80% power to test a hypothesised CBR of ≥35% against an unfavourable CBR of ≤20%. If ≥ 17 patients achieved benefit, the null CBR of 20% would be rejected at a nominal 5% alpha level. Secondary end points included progression-free survival (PFS), overall survival (OS), quality of life and serum biomarkers. Findings: Fifty-six patients were enrolled from May 2015 to February 2019 and are included in the intention-to-treat analysis. Median PFS was 3.67 (2.62–7.25) months. Median OS was 14.16 (95% confidence interval [CI]: 8.4-NR) months, CBR = 39.29% (22/56) (CI = 0.265–0.533, p = 0.0007). No new or unexpected adverse events were seen. The most common grade I–II events were diarrhoea, nausea and fatigue. The most common grade III–IV events were hypertension and liver function test abnormalities. Interpretation: These data suggest that there is a benefit to front-line pazopanib in patients with STS who are not candidates for cytotoxic chemotherapy. Highlights: phase II of upfront pazopanib in patients with advanced soft-tissue sarcoma who were unfit for chemotherapy. The dose of pazopanib escalated from 200 mg BID to 800 mg daily. 39.3% (22/56) clinical benefit rate, 3.67 month progression-free survival, and 14.16 month overall survival with a single agent pazopanib. The regimen was well-tolerated with most adverse events at grade I–II. Pazopanib is a safe and effective front-line option in those unfit for chemotherapy.